User-Centered Decentralized p2p Energy Trading Model for Managing Line Congestion in Energy Communities - Garcia-Munoz, F; Davila-Galvez, S (Elsevier Ltd, 2025)
This paper presents a user-centered, fully decentralized framework to allow an energy community (EC) to self-manage line congestion issues through peer-to-peer (P2P) energy trading and a flexibility market using the users’ distributed energy resources (DERs) assets to take an energy seller (buyer) role when they have a surplus (deficit). A three-stage optimization-based model is introduced to consider the users’ preferences and identify line congestion issues using the Distflow model to evaluate the distribution network (DN) limitations. In this regard, users maximize their benefits in the first optimization stage by optimizing their DER operation. In the second stage, the distribution system operator (DSO) solves an optimal power flow model to identify potential congestion given the users’ preferences. If congestion occurs, the third stage activates a P2P energy and flexibility market designed to resolve the issue by minimizing deviations from the users’ initial preferences. To achieve full decentralization, a two-step alternating direction method of multipliers (ADMM) algorithm is employed: the first step addresses optimal power flow, while the second manages the P2P and flexibility market. Tests were conducted on a 33-bus DN for different DER penetration levels, showing that the methodology efficiently meets energy requirements while respecting the network s physical constraints and improving information security. © 2025 Elsevier Ltd